LITERATURE ANALYSIS ON THE ROLE OF ARTIFICIAL INTELLIGENCE IN STRENGTHENING CYBERSECURITY IN E-GOVERNMENT SERVICES - Erfan Wahyudi; Wiredarme (Ninety Media Publisher, 2026)
The rapid expansion of e-government services has increased the importance of cybersecurity in protecting public digital infrastructure, citizen data, and the continuity of government operations. In this context, Artificial Intelligence (AI) has emerged as a promising approach to strengthening cyber defense through real-time monitoring, anomaly detection, intelligent classification, and adaptive threat response. This study examines the role of AI in strengthening cybersecurity in e-government services through a Systematic Literature Review (SLR) of 27 selected articles published between 2019 and 2025. The review synthesizes the literature at the intersection of AI, cybersecurity, and digital government to identify major research trends, dominant methodological approaches, thematic classifications, and key implementation challenges. The findings show that AI is increasingly positioned not only as a tool for improving administrative efficiency, but also as a strategic enabler of cyber resilience in public-sector digital ecosystems. The literature highlights that machine learning, deep learning, explainable AI, anomaly detection, and privacy-preserving learning models have substantial potential for improving the security of citizen portals, digital identity systems, inter-agency platforms, and smart-government infrastructures. However, implementation remains constrained by fragmented data environments, interoperability problems, institutional readiness gaps, limited explainability, privacy concerns, and the dual-use nature of AI in cyber defense and cyber offense. This study concludes that AI is most effective when integrated into a broader socio-technical framework encompassing governance, accountability, transparency, and organizational capacity.